2018
DOI: 10.1016/j.lwt.2018.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and rheological properties of rice-based gluten-free blends containing differently treated chickpea flours

Abstract: This study focused on the evaluation of the physicochemical and rheological properties of chickpea flours and blends obtained by partially substituting rice flour (25%) with raw, roasted and dehulled chickpea flour. The characteristics of the resultant doughs were evaluated. In comparison with rice flour, blends containing chickpea flours exhibited high protein and fat content, a reduced retrogradation tendency (setback values of 404-415 vs. 479 BU) and a higher foaming capacity and stability, which can be ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 23 publications
4
20
0
Order By: Relevance
“…It could be observed from Table 2 that G 0 and G 00 increased with the rise in frequency from 1.25365 to 125.367 rad/s. Similar results were also reported by Kahraman et al (2018). This suggested that both viscous and elastic character simultaneously increased with higher frequency.…”
Section: Dynamic Frequency Sweep Measurements Of Chickpea Flat Bread Doughsupporting
confidence: 89%
“…It could be observed from Table 2 that G 0 and G 00 increased with the rise in frequency from 1.25365 to 125.367 rad/s. Similar results were also reported by Kahraman et al (2018). This suggested that both viscous and elastic character simultaneously increased with higher frequency.…”
Section: Dynamic Frequency Sweep Measurements Of Chickpea Flat Bread Doughsupporting
confidence: 89%
“…It was observed that with the incremental addition of EF, the values of both G′ and G″ of composites were increased but their values remained lower than that of control. A similar effect for both G′ and G″ was observed in rice‐based GF formulations containing chickpea flour (Kahraman, Harsa, Lucisano, & Cappa, 2018).…”
Section: Resultssupporting
confidence: 65%
“…For pasting properties of silkworm pupae powder, EAP had the highest peak viscosity (PV), trough (TV), breakdown (BD), final viscosity (FV) and setback (SB) (Table 6). The pasting behaviour of EAP was different in viscosity values (PV, TV, BD, FV and SB) compared with rice, wheat and tapioca flours (Setyawati et al, 2016;Kahraman et al, 2018). Especially, setback values of silkworm pupae powder (36.03-147.58 RVU) were higher than other flours, that is, rice flour (57 RVU) (Zhou et al, 2003) and wheat flour (20.1 RVU) (Zaidul et al, 2007).…”
Section: Physical Qualitiesmentioning
confidence: 92%